‘A deep, empathetic, wondrous connection’: Autistic adults' definitions and experiences of nature connection - Samantha Friedman; Sara McHaffie; Roan Noble; Anna Stenning (People and Nature)
Abstract Connection to nature is an important concept for understanding human‐nature relationships, interests in nature and pro‐environmental behaviours. However, conceptualisations of this relationship thus far have excluded autistic perspectives. Through this reflexive thematic analysis of survey responses from 108 autistic participants in the UK, we sought to understand how autistic people define and experience connection to nature. Towards this aim, we developed three themes: ‘feeling that you benefit nature and nature benefits you’; ‘connecting with something ancient to which I nevertheless belong’; and ‘it makes me a little sad tbh.’ Across many participants in this sample, nature was not something they saw as separate from themselves (or from humans more generally), and so connection to nature was not a simple, unidirectional relationship nor a clear‐cut binary. Through this work, we hope to contribute towards the effort to imbue ecopsychology and related fields with the influences of critical disability studies. Read the free Plain Language Summary for this article on the Journal blog.